Pengaruh Promo Flash Sale dan Viral Marketing terhadap Keputusan Pembelian Produk Erigo - Fardani, Efrian; Siregar, Salim (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Indonesia has more than 275 million inhabitants. So that the number of internet users in Indonesia has increased every year. The Internet makes consumer behavior change. From doing shopping in person or face to face then changing to shopping online. the product category that Indonesians are most looking for when shopping online is the fashion and accessories category in 2021. Fashion is closely related to clothing, therefore clothing is a human need which is a tool to cover and protect the body. In this study discusses the effect of flash sale promos and viral marketing on purchasing decisions. This study discusses Erigo where the research object is Erigo's Instagram followers. This study uses path analysis with SPSS and Excel tools. The results showed that the influence of paris from flash sale promo and viral marking variables on purchasing decisions was 16.5% and 4% respectively with a total simultaneous effect of 20.5%. While the remaining 79.5% is influenced by other variables not examined. Keywords : flash sale promotion; viral marketing; purchase decisions.